2023
DOI: 10.1063/5.0137424
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Ga-doped AlN nanowires

Abstract: We show that intentional Ga doping of AlN nanowires in the 0.01%–0.5% range leads to the spontaneous formation of nanometric carrier localization centers. Accordingly, for single nanowires, we observed a collection of sharp cathodoluminescence lines in a wavelength range spanning from 220 to 300 nm. From temperature-dependent cathodoluminescence, a ratio between the intensity at room temperature and 5 K of 20–30% is measured. We found that an ensemble of Ga-doped AlN nanowires exhibits a wide-band cathodolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…We note that the N-rich conditions used here likely favor the formation of Al vacancies [80][81][82][83] and that O is a common background impurity in self-assembled GaN NWs grown by MBE [84]. No intense transitions are seen around 5 eV as sometimes reported for AlN NWs grown on GaN stems [36,85]. The band-edge is 75-105 meV wide, which is narrower than for AlN NWs grown on GaN stems [36,85] but broader than for direct MBE growth of AlN NWs on Si substrates (20-50 meV) [69,71], and than for vapor phase epitaxy of strain-free AlN layers (≈1 meV) [71]).…”
Section: Point Defect Incorporationsupporting
confidence: 63%
See 1 more Smart Citation
“…We note that the N-rich conditions used here likely favor the formation of Al vacancies [80][81][82][83] and that O is a common background impurity in self-assembled GaN NWs grown by MBE [84]. No intense transitions are seen around 5 eV as sometimes reported for AlN NWs grown on GaN stems [36,85]. The band-edge is 75-105 meV wide, which is narrower than for AlN NWs grown on GaN stems [36,85] but broader than for direct MBE growth of AlN NWs on Si substrates (20-50 meV) [69,71], and than for vapor phase epitaxy of strain-free AlN layers (≈1 meV) [71]).…”
Section: Point Defect Incorporationsupporting
confidence: 63%
“…No intense transitions are seen around 5 eV as sometimes reported for AlN NWs grown on GaN stems [36,85]. The band-edge is 75-105 meV wide, which is narrower than for AlN NWs grown on GaN stems [36,85] but broader than for direct MBE growth of AlN NWs on Si substrates (20-50 meV) [69,71], and than for vapor phase epitaxy of strain-free AlN layers (≈1 meV) [71]). We associate the broad transition in our AlN NWs to the presence of a large density of ionized donors [86].…”
Section: Point Defect Incorporationmentioning
confidence: 58%
“…Accordingly, the emission lines observed below 240 nm (which corresponds to 1 ML) are assigned to the recombination of confined carriers in these incomplete QWs, with a lateral size smaller or comparable to the 2.8 nm GaN Bohr exciton radius. Emission lines above 240 nm are attributed to larger 3D GaN clusters which have also been observed [21]. They are however out of the scope of this study.…”
mentioning
confidence: 54%
“…The heterostructure consists of a 500 nm long highly conductive n-GaN stem, followed by a 150 nm n-type AlN section, a 30 nm Ga-doped AlN active area, a 150 nm long p-type AlN section, and a 15 nm p-type GaN cap, measured based on secondary electron contrast from the image acquired by scanning electron microscopy (SEM). The AlGaN active area section was grown with an extremely low Ga content of at most 1%, as measured by energy-dispersive X-ray spectroscopy (EDX) . This value, however, does not correspond to the Ga composition of the AlGaN clusters but to an averaged value over the NW diameter.…”
Section: Introductionmentioning
confidence: 99%
“…These optical properties are in line with Ga-rich AlGaN clusters resulting from Ga doping of AlN NWs. A detailed study of such features has been carried out and can be found in ref . The presence of an additional peak only at low temperature centered at around 325 nm is assigned to larger AlGaN clusters.…”
Section: Introductionmentioning
confidence: 99%